2010
DOI: 10.1097/rlu.0b013e3181fa62f8
|View full text |Cite
|
Sign up to set email alerts
|

Metastases of Germ Cell Tumor Mimicking Paget's Disease

Abstract: A bone scan done for a 58-year-old man with intense pain in the lower back and pelvis, showed intense MDP uptake in most of the pelvis, in the proximal aspect of the left femur, D-8 vertebra, and a focal area of uptake in the skull. The features were suggestive of Paget's disease. An x-ray of pelvis revealed multiple sclerotic lesions in the pelvis (left ischium, acetabulum, and supra-acetabular regions of left ilium, right acetabulum, the left femoral neck, and left hip joint), suggesting metastases. On clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…1 However, a few cases in the literature have demonstrated that metastatic lesions from germ cell tumor and hepatocellular carcinoma have mimicked radiotracer uptake patterns classically seen in Paget disease. 7,8 Considering this, it is important to keep metastatic disease in the differential diagnosis when such diffuse vertebra uptake involving the body, posterior elements, transverse, and spinous processes is seen on whole-body radionuclide bone scan, as such appearance can also be caused by other entities, especially in the presence of multifocal osseous disease as was seen in our case in a patient with prostate cancer.…”
Section: Figurementioning
confidence: 73%
See 1 more Smart Citation
“…1 However, a few cases in the literature have demonstrated that metastatic lesions from germ cell tumor and hepatocellular carcinoma have mimicked radiotracer uptake patterns classically seen in Paget disease. 7,8 Considering this, it is important to keep metastatic disease in the differential diagnosis when such diffuse vertebra uptake involving the body, posterior elements, transverse, and spinous processes is seen on whole-body radionuclide bone scan, as such appearance can also be caused by other entities, especially in the presence of multifocal osseous disease as was seen in our case in a patient with prostate cancer.…”
Section: Figurementioning
confidence: 73%
“…The presence of “Mickey Mouse sign” on radionuclide bone scan is reported to be more suggestive of Paget disease than metastasis, even in patients with cancer with a positive predictive value of 88% when patients who had definite evidence of multiple metastases were excluded and 70% when they were included 1 . However, a few cases in the literature have demonstrated that metastatic lesions from germ cell tumor and hepatocellular carcinoma have mimicked radiotracer uptake patterns classically seen in Paget disease 7,8 . Considering this, it is important to keep metastatic disease in the differential diagnosis when such diffuse vertebra uptake involving the body, posterior elements, transverse, and spinous processes is seen on whole-body radionuclide bone scan, as such appearance can also be caused by other entities, especially in the presence of multifocal osseous disease as was seen in our case in a patient with prostate cancer.…”
mentioning
confidence: 99%